A preliminary risk assessment on development the fuel gas supply system of a small LNG fueled fishing ship. (15th August 2022) - Shao, Yude; Kang, Ho-Keun; Lee, Yoon-Hyeok; Królczyk, Grzegorz; Gardoni, Paolo; Li, Z.X.
Abstract: Liquefied natural gas (LNG) as an alternative marine fuel is attracting interest from a variety of parties in its use for large and small ships due to the role in improving climate change. However, a broader range of ships including in particular ferries, cargo and offshore support ships is operating with dual-fuel LNG engines. Compared to the conventional marine fuels, the use of LNG could offer an attractive alternative in the fishing industry for reducing exhaust gas emissions in the air in terms of NOx, SOx, CO2, and particle matter (PM), as well as possible economic benefits. In the context mentioned above, our research team has been developing a concept design for small LNG fueled fishing ships. A Hazard Identification (HAZID) study was carried out as one of the essential stages throughout the unique system development of the LNG fueled fishing ship. The HAZID study was done to gain a better understanding of the proposed idea and to identify the significant difficulties or risks that could jeopardize the unique fishing ship design's safety. For hazards with unacceptable risks or as low as reasonably possible (ALARP), additional course of actions and recommendations were discussed and proposed in the safety action register. The results of this study will help the naval architects to follow up the detailed system designs. Highlights: A HAZID study on development the FGSS of a small fishing ship fueled by natural gas. Heat and mass balance for the FGSS was calculated by process simulator. An ALARP principle was utilized to enhance the overall safety of the system. A safety action register was proposed with safety actions and recommendations.